Respuesta :
Answer:
Step-by-step explanation:
A) 12x² y⁵z = 2² * 3 * x² * y⁵ * z
150x⁶y⁵z = 5² * 2 * 3 * x⁶ * y⁵ * z
66y⁹z = 2 * 3 * 11 * y⁹ * z
GCF = 2 * 3 * y⁵ * z = 6y⁵z
B) 4x² - 40x + 100 = (2x)² - 2 * 2x * 10 + 10²
= (2x - 10)²
C) 81x² - 64 = (9x)² - 8² {a² - b² = (a + b)(a - b)}
= (9x + 8)(9x - 8)
D) (a + b)² = a²+ 2ab + b²
E) a² - b² = (a + b)(a - b)
Answer:
Simplifying 4x2y + 12xy2 + 9y3 Reorder the terms: 12xy2 + 4x2y + 9y3 Factor out the Greatest Common Factor (GCF), 'y'. y(12xy + 4x2 + 9y2) Factor a trinomial.
Step-by-step explanation:
Subtracting Perfect Squares · (a+b)(a-b)=a2-b · Example · 4x2-9= · Subtracting Perfect Cubes · a3-b3=(a-b)( · Adding Perfect Cubes · x3+27=(x+3)(x2-3x+9).